Decoding the body language of immunity: Tackling the immune system at the organism level. Issue 18 (December 2019) - Chevrier, Nicolas
Abstract: The immune system is a dynamic mesh of molecules, cells, and tissues spanning the entire organism. Despite a wealth of knowledge about the components of the immune system, little is known about the general rules governing the organismal circuitry of immunity. Deciphering the immune system at the scale of the whole organism is crucial to understanding fundamental problems in immunobiology and physiology, and to manipulate immunity for maintaining health and preventing disease. Here I discuss the emerging principles of interorgan communications during immune responses by focusing on three common themes: the regulation of the ( i ) composition, ( ii ) condition, and ( iii ) coordination of communicating organs by molecular and cellular factors. Based on these common principles, I emphasize fundamental gaps in our knowledge of organismal immune processes and the outlook to tackle immunity at the scale of the whole organism.